Pengaruh board gender diversity, profitabilitas, sales growth, risiko bisnis struktur aset dan CEO tenure terhadap struktur modal pada perusahaan sektor energi periode 2019-2023 - Resita Jati Wasesa (Universitas Negeri Surabaya, 2025)
This research seeks to explore how gender diversity within boards of directors influences capital structure, alongside examining the roles of profitability, revenue growth, business risk, asset composition, and CEO tenure. The focus is on energy companies listed on the Indonesia Stock Exchange between 2019 and 2023. Utilising a quantitative approach, the study relies on secondary data sources. The sample comprises firms in the energy sector that were publicly traded on the IDX during the specified years, selected through purposive sampling. Panel data regression analysis was employed using STATA version 17 to process the data. The results indicate that CEO tenure has a significant negative impact on the capital structure of energy companies. In relation to the length of the CEO's tenure, a company may appoint an experienced CEO as it reflects their understanding of the mechanisms of debt ratio usage and the associated risks. However, no significant relationships were found concerning gender diversity on the board of directors, profitability, sales growth, business risk, or asset structure. Therefore, companies in the energy sector should consider additional factors beyond these five variables to attain an optimal capital structure. Company management has the freedom to recruit members of the board of directors in terms of gender diversity. Management must maintain stable profitability so that creditors or investors can better consider the level of profitability when assessing the capital structure. Management should also ensure stable sales growth to avoid selling products on credit. Furthermore, the company’s management is expected to choose between external and internal funding appropriately. Lastly, management must maintain financial stability, as it reflects the company's ability to meet long-term fixed asset requirements.